Modeling Vector Fields in Space of Affine Connection - Tadeyev, Petro (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The authors have been constructed the splitting of the basic geometric images vector field (points, straights, hyperplanes and hyperguadrics) in transition from n-dimensional affine space to the space of affine connection. All invectigations have been fulfilled in the moving coordinate system of zero order.